Effects of In-Season Strength Training on Physical Fitness and Injury Prevention in North African Elite Young Female Soccer Players - Manel Darragi; Hassane Zouhal; Mariem Bousselmi; Houssem M. Karamti; Cain C. T. Clark; Ismail Laher; Anthony C. Hackney; Urs Granacher; Amira B. M. Zouita (SpringerOpen, 2024)
Abstract Background Strength training (ST) primarily enhances physical fitness (e.g., muscle strength, power, speed) and bone density in female soccer players. Less information is available on the injury preventive effects of ST in female athletes. Accordingly, this study aimed to investigate the effects of a 12-week in-season ST on measures of physical fitness and injury occurrence in young elite female soccer players. Methods Thirty elite female soccer players (15.4 ± 1.9 years; maturity offset + 2.3 ± 1.1 years) participated in this study, and were randomly assigned to a strength training group (STG, n = 14) or an active control (CG, n = 16) group. ST lasted twelve weeks and included full body muscle strengthening exercises using primarily weight machines at progressive intensities ranging between 40 and 85% of the one-repetition-maximum (1-RM). The CG practiced a traditional soccer training program. Overall, training volumes of the two groups were similar with a training load (rating of perceived exertion × time) of 1158.4 ± 67.7 arbitrary unity (AU) for the STG and 1188.8 ± 44.1 AU for the CG. Pre and post training, the following physical fitness tests were applied: dynamic muscle strength (relative [to body mass] and absolute 1-RM bench/leg press, lat-pull down), jump performance (countermovement jump [CMJ], squat jump [SJ], five-jump-test [5JT]), linear-sprint speed (5-m, 10-m, 30-m), change-of-direction speed (T-test with and without ball), sport-specific performance (Yo-Yo Intermittent Level1 [YYIRTL1], and repeated shuttle sprint ability [RSSA]). The injury rate per 1000-h exposure was monitored throughout the soccer season. Results No significant baseline differences were observed between groups. Statistically significant group-by-time interactions were found for absolute (p < 0.001, d = 2.59) and relative 1-RM bench press (p < 0.001, d = 2.39), absolute 1-RM lat-pull down (p < 0.001, d = 1.68), and relative 1-RM leg press (p < 0.001, d = 1.72). Significant group-by-time interactions were observed for CMJ (p = 0.005, d = 1.27), RSSAmean (p = 0.007, d = 0.81), and RSSAtotal (p < 0.001, d = 1.90). Post-hoc tests indicated that the STG group demonstrated greater improvements in all tested variables compared to CG (1.2 < d < 2.5). However, no significant interaction effects were noted for measures of linear sprint speed and YYIRTL1 performance. Additionally, non-contact injuries during the season were significantly lower (p = 0.003, d = 1.31) in the STG (0.48/1000 h of exposure) than the CG (2.62/1000 h of exposure). Conclusions Twelve weeks of an in-season ST resulted in larger physical fitness improvements and fewer injuries compared with an active control in elite young female soccer players. Accordingly, ST should be systematically applied in female soccer to enhance performance and prevent injuries.